Invisible, intangible, irrelevant, yet inevitable? Qualitative insights into consumer perceptions of heating tariffs and drop-in renewable gases in the German domestic heating market. (September 2022) - Rilling, Benedikt; Herbes, Carsten
Abstract: One of the key challenges of increasing renewable energy use is consumer demand. In the residential heating sector, where long-lived fossil-fuel systems are slow to be replaced, consumer demand for drop-in renewable gases like biomethane or Synthetic Natural Gas could play an important role in short-term decarbonization. As this sector is a major emitter of CO2 in Europe, robust green demand could be key to fulfilling the targets set in the Paris Agreement. Yet existing research focuses on the supply side and technical aspects of renewable gases, leaving the demand side and consumer preferences for these gases largely neglected. To close this gap, we conducted a qualitative study based on two empirical strands: 22 interviews with heating consumers, and a set of interviews and focus groups with 27 industry experts. The study was situated in Germany, one of the world's largest biogas producers. Our results show that choosing a heating tariff is a low-involvement decision, but one made by a complex calculus where the environmental benefits of renewable gases count positively, but large-scale biogas production and perceived energy crop monocultures count negatively. SNG is still largely unknown and regarded neutrally. Industry experts evaluate voluntary markets for renewable gases as small, cost-driven and made up of consumers accustomed to low-cost products. Our insights on consumers who have the decision-making power over their heating tariffs can help policy makers support voluntary renewable energy markets and provide energy practitioners with approaches to increasing consumer engagement with their products. Highlights: We conducted a qualitative approach to elicit preferences for renewable gas products. Choosing a heating tariff is for consumers a low-involvement decision. Biomethane and biogas are known, but their evaluation is controversial. Synthetic Natural Gas is largely unknown and evaluated neutrally. Marketing renewable gases requires strategies for consumer engagement.